Muhammadiyah: A Preliminary Study - Azra, Azyumardi (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1994)
This article is a collection of Bibliography reviewer that discuss Muhammadiyah. The following are some of the bibliography were reviewed:A.R. Sukrianta dan Abdul Munir Malkhan, Perkembangan Pemikiran Muhammadiyah dari Masa ke Masa: Menyambut Muktamar ke-41, (Yogyakarta: Dua Dimensi, 1985).A.R. Sukriyanto dan Abdul Munir Mulkhan, Pergumulan Pemikiran dalam Muhammadiyah, (Yogyakarta: Sipress, 1990).Ruslan Abdul Gani. et.al., Cita dan Citra Muhammadiyah, (Jakarta: Pustaka Panjimas, 1985).M.T. Arifin, Gagasan Pembaharuan Muhammadiyah, (Jakarta: Pustaka Jaya, 1987).M.T. Arifin, Muhammadiyah: Potret yang Berubah, (Surakarta: Institut Gelanggang Pemikiran Filsafat Sosial Budaya dan Kependidikan, 1990).M. Yusron Asrofie, Kiyai Haji Ahmad Dahlan, Pemikiran dan Kepemimpinannya, (Yogyakarta: Yogyakarta Offset, 1983).Fathurrahman Djamil, Ijtihad Muhammadiyah dalam Masalah-masalah Fiqh Kontemporer, (Jakarta: Doctoral Dissertation the State Institute of Islamic Studies (IAIN), 1994).Yunahar Ilyas. et.al., Muhammadiyah dan NU: Reorientasi Wawasan Keislaman, (Yogyakarta: LPPI UMY, LKPSM NU, & PP al-Muhsin, 1993).Musthafa kamal, Chusnan Yusuf, dan Rosyad Sholeh, Muhammadiyah sebagai Gerakan Islam, (Yogyakarta: Penerbit Persatuan, 1976).M. Rusli Karim, Muhammadiyah dalam Kritik dan Komentar, (Jakarta: Rajawali, 1986).Arbiyah Lubis, Pemikiran Muhammadiyah dan Muhammad Abduh: Suatu Studi Perbandingan, (Jakarta: Doctoral Dissertation the State Institute of Islamic Studies (IAIN), 1989).Abdul Munir Mulkhan, Pemikiran K.H. Ahmad Dahlan dan Muhammadiyah dalam Perspektif Perubahan Sosial, (Jakarta: Bumi Aksara, 1990).Abdul Munir Mulkhan, Pak AR Menjawab 245 Permasalahan dalam Islam, (Yogyakarta: Sipress, 1990).M. Din Syamsuddin, Muhammadiyah Kini dan Esok, (Jakarta: Pustaka Panjimas, 1990).H.S. Prodjokusumo, Melestarikan Muhammadiyah, (Jakarta: Pimpinan Pusat Muhammadiyah, 1985).Yusuf Abdullah Puar, Perjuangan dan Pengabdian Muhammadiyah, (Jakarta: Pustaka Antara, 1989).Sahlan Rosidi, Kemuhammadiyahan untuk Perguruan Tinggi, (Solo: Penerbit Mutiara, 1982).Usman Yatim dan Almisar Hamid, Muhammadiyah dalam Sorotan, (Jakarta: Bina Rena Pariwara, 1993).The Central Committee of Muhammadiyah, Mengkaji Muhammadiyah, (Jakarta: 1982).The Central Committee of Muhammadiyah, Menuju Muhammadiyah, (Yogyakarta: 1984). DOI: 10.15408/sdi.v1i2.863